DJM-CYBER: A Joint Master in Advanced Cybersecurity - Danidou, Yianna; Ricci, Sara; Skarmeta, Antonio; Hošek, Jiří; Zanero, Stefano; Lendak, Imre (ACM, 2023)
Various publicly available studies show that millions of cybersecurity experts are missing worldwide. One possible way to tackle the workforce gap is with tailored higher education programmes. The goal of this paper is to present the relevant projects and frameworks of the European Union which can guide the development of novel cybersecurity education offerings. We describe the most relevant and freely available tools and test them in the development of a joint Master study programme to be offered by a consortium of five European universities. We show that these tools allow educators and study programme developers to map their outputs to the European Cybersecurity Framework developed by the ENISA and other similar frameworks. We complete our work with a detailed analysis of a joint cybersecurity master programme consisting of four innovative and distinctly different tracks.

Various publicly available studies show that millions of cybersecurity experts are missing worldwide. One possible way to tackle the workforce gap is with tailored higher education programmes. The goal of this paper is to present the relevant projects and frameworks of the European Union which can guide the development of novel cybersecurity education offerings. We describe the most relevant and freely available tools and test them in the development of a joint Master study programme to be offered by a consortium of five European universities. We show that these tools allow educators and study programme developers to map their outputs to the European Cybersecurity Framework developed by the ENISA and other similar frameworks. We complete our work with a detailed analysis of a joint cybersecurity master programme consisting of four innovative and distinctly different tracks.
DJM-CYBER: A Joint Master in Advanced Cybersecurity
Keywords: Cybersecurity Education; Joint Master Programme; Cybersecurity Roles; Cybersecurity Profiles; ENISA ECSF; NICE Framework; Cybersecurity Education; Joint Master Programme; Cybersecurity Roles; Cybersecurity Profiles; ENISA ECSF; NICE Framework